ANALISIS STRATEGI MEREK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA J.CO DONUTS & COFFEE CABANG CAMBRIDGE CITY SQUARE MEDAN - Nina Adriani; Beby Karina Fawzeea Sembiring (Universitas Sumatera Utara, 2013)
J.CO Donuts & Coffee representing one of brand fast food with one of the best food in J.CO is donut. Donut is represent food which have recognized by society, but attendance of J.CO Donuts & Coffee have earned to draw consumer and become gossips one day after its apparition.This study aims to determine the influence of brand strategy and brand image to the purchasing decision in J.CO Donuts & Coffee branch at Cambridge City Square Medan. Formulation problem in this research is how far brand strategy and brand image influencing purchasing decisions in J.CO Donuts & Coffee branch Cambridge City Square Medan.The population in this study were all customers J.CO Donuts & Coffee branch at Cambridge City Square Medan who has purchased decisions whose numbers are unknown. This research is descriptive quantitative research, and data used are primary and secondary data obtained through the study of the measurement documentation and questionnaires using likert scale. The analysis method used is descriptive analysis method and the multiple regression analysis method.The results of this study indicate that simultaneous brand strategy, and brand image has positive and significant impact on purchase decisions J.CO Donuts & Coffee branch at Cambridge City Square Medan. Partially brand image can be seen that the variable is the dominant variable influencing the purchase decision in J.CO Donuts & Coffee branch at Cambridge City Square Medan. Value Adjusted R Square = 0.204, mean 20,4% purchase decision factors can be explained by the independent variable (brand strategy and brand image ) while the remaining 79,6% is explained by other factors not examined in this study like location and price.Keywords: brand strategy, brand image and purchasing decisions.